If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -9x = 133 + -37x Solving 13 + -9x = 133 + -37x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '37x' to each side of the equation. 13 + -9x + 37x = 133 + -37x + 37x Combine like terms: -9x + 37x = 28x 13 + 28x = 133 + -37x + 37x Combine like terms: -37x + 37x = 0 13 + 28x = 133 + 0 13 + 28x = 133 Add '-13' to each side of the equation. 13 + -13 + 28x = 133 + -13 Combine like terms: 13 + -13 = 0 0 + 28x = 133 + -13 28x = 133 + -13 Combine like terms: 133 + -13 = 120 28x = 120 Divide each side by '28'. x = 4.285714286 Simplifying x = 4.285714286
| x+2n=5n+23 | | 3x+(2/5)=4x+(4/5) | | (8x+12)=((5x-5)2) | | 6x-7=79-2x | | 9+4x=18x | | 9y-10=5y-54 | | 6x^4-12x^2= | | (3-4)+4*3*-3= | | 72x^2+56x/9x-7 | | 7(2x-8)-6=14x-62 | | 4(m-2)-7+2m=6(m+5) | | (8x+12)=(5x-5) | | 3z+7=35 | | 6(1/3)= | | 0*X=5 | | 8r+-5=51 | | 16+-9-2(4*3*1/2)= | | 8/3-2i | | -10+2m=8 | | 90+.4x=X | | 16+x^2=49 | | 5/4a+2=22 | | 8/(3-2i) | | 9y+-10=5y+54 | | -4(3y-10)+2(2y+9)= | | 4/3p=16 | | h(t)=5t^2-30t+45 | | 3/2n=15 | | 2(-3)+16-(3+4)= | | B=900(1+.02) | | d/5+4=9 | | 24-6x=24 |